Analyses of RC Columns in a Variety of Sizes. (2015) - Kinoshita, Koji; Yamamoto, Shogo
Abstract: Large-scale RC column tests have been performed in Japan at both the E-defense and JR-Tokai test facility and in United States at the University of California, San Diego Large Outdoor Shake Table Testing Facility. Such recent large-scale RC column tests have been compared with results of small-scale RC column tests. As a result, results of these large-scale model experiments show shortcomings in small-scale model experiments. At least one study showed that the small-scale model does not reproduce the observed damage on the large-scale model. Therefore, in order to develop small-scale model experiment results, experiment tests of small-scale model which might agree well with large-scale model should be undertaken. In an authors' previous study, experimental cyclic loading study on 0.1- and 0.2-scale RC column models was carried out and results have been compared with full- and 0.5-scale RC column models performed in the JR-Tokai test facility. Although the authors' experimental study clearly shows agreements and differences between large-scale model and small-scale model, the results still remain to be validated with respect to bond behavior between longitudinal steel bars and concrete. This study analyses full-, 0.5-, 0.2-, and 0.1-scale RC columns models using fiber model analyses to investigate the bond behavior analytically. This analytical study focuses on differences in hysteresis curves. Validity of the analysis results was determined by comparing experimental results of full- and 0.5-scale model. It is shown that fiber model analysis results agree well with the full- and 0.5-scale model. Although results of 0.1-scale models, which are scaled correctly for not only steel bar radius but also steel bar ribs, are capable to full- and 0.5scale model, analytical results of 0.2- and 0.1-scale model with different steel bar ribs seem to be less agreements. Therefore, it is shown that one of the causes of shortcomings in small-scale models is the difference of bond behavior between longitudinal steel bars and concrete.